FGFR2 inhibition in Cholangiocarcinoma - Vogel, Arndt; Segatto, Oreste; Stenzinger, Albrecht; Saborowski, Anna (Annual review of medicine, 2023)
Biliary tract cancer (BTC) is the second most common primary liver cancer after hepatocellular carcinoma and accounts for 2% of cancer-related deaths. BTCs are classified according to their anatomical origin into intrahepatic (iCCA), perihilar, or distal cholangiocarcinoma, as well as gall bladder carcinoma. While the mutational profiles in these anatomical BTC subtypes overlap to a large extent, iCCA is notable for the high frequency of IDH1/2 mutations (10-22%) and the nearly exclusive occurrence of FGFR2 fusions in 10-15% of patients. In recent years, FGFR2 fusions have become one of the most promising targets for precision oncology targeting BTC, with FGFR inhibitors already approved in Europe and the United States for patients with advanced, pretreated iCCA. While the therapeutic potential of nonfusion alterations is still under debate, it is expected that the field of FGFR2-directed therapies will be subject to rapid further evolution and optimization. The scope of this review is to provide an overview of oncogenic FGFR signaling in iCCA cells and highlight the pathophysiology, diagnostic testing strategies, and therapeutic promises and challenges associated with FGFR2-altered iCCA.
First published as a review in advance on September 28, 2022
Gesehen am 22.03.2023